(untitled) (Research, Society and Development, 2022)
Objectives: The study aimed to understand the practices and knowledge of riverside women regarding climacteric and self-care. Methodology: Descriptive exploratory study, with a qualitative approach, carried out with riverine women living in communities located along the left bank of the Amazon River. Data collection took place through semi-structured interviews with 24 women aged between 40 and 65 years old. Leininger’s thematic analysis method was used. Results: Twenty-four riverside dwellers participated in the study. Twenty (20) lived with a partner, twelve (12) did not have high school and nine (9) were housewives. Three categories were identified: 1) Riverside women: Perceiving and experiencing the climacteric/menopause 2) Riverside women and self-care experiences and 3) Riverside women experiencing health care systems. Women have knowledge about self-care, passed from generation to generation, and the use of medicinal plants. Final Considerations: Riverside women have knowledge about Climacteric and make use of popular knowledge and practices and the biomedical model for their self-care. The study reinforces the importance of bringing scientific and popular knowledge closer together, promoting the exchange of knowledge and experiences and, consequently, a better quality of life for riverside dwellers.